Ergonomics Through the Lens of Gamification - Medved, Tilen; Okreša Đurić, Bogdan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Our paper explores the connection between ergonomics and gamification in order to understand the relationship between the two areas and their impact on employee health, comfort and productivity. We outline the key ergonomic principles for creating an ergonomically designed work environment, such as maintaining a neutral posture, encouraging movement and stretching, and managing excessive workload. In addition, we look at gamification – a strategy that uses game-specific concepts, including badges, leaderboards and challenges – to motivate and engage employees. This paper provides use-case examples that enable organizations to integrate ergonomics through engaging, game-like elements by linking ergonomic principles with different gamification methods. With this approach, organizations can cultivate a proactive well-being culture that ultimately improves employee satisfaction and overall organizational performance.